PSYCHOLOGICAL ADAPTATION OF YOUNG SPECIALISTS TO THE CONDITIONS OF EDUCATIONAL INSTITUTIONS: CHALLENGES, DETERMINANTS AND SUPPORT MECHANISMS. - Orifjonova. N (International Journal of Literature and Language Studies, 2026)
Abstract. The successful integration of young specialists into educational institutions is considered one of the critical factors influencing educational quality and professional sustainability. The transition from higher education to professional teaching practice is often accompanied by psychological, social, and organizational challenges that may affect job satisfaction, professional identity, and long-term career commitment. The present study examines the psychological adaptation of young specialists within educational institutions and identifies the key factors influencing their adaptation process. The research is based on the analysis of contemporary psychological and pedagogical literature and empirical findings related to novice teachers’ adaptation. The study reveals that professional adaptation is a multidimensional phenomenon encompassing emotional stability, professional competence, social integration, organizational support, and self-efficacy. Findings indicate that mentoring programs, supportive organizational climates, effective communication, and professional development opportunities significantly facilitate successful adaptation. Conversely, excessive workload, role ambiguity, lack of institutional support, and emotional stress contribute to maladaptation. The study emphasizes the necessity of systematic psychological support mechanisms for novice specialists and proposes practical recommendations for educational institutions to strengthen adaptation processes and enhance professional effectiveness.